COOPERATIVE LEARNING PRACTICE - Syafrizal, Syafrizal; Pahamzah, Jhon (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2006)
The ultimate goal of the English language teaching and learning is that learners can use the language in an accepted level of appropriacy. To achieve the goal of teaching, teachers should determine the appropriate strategy of the teaching Â·and learning. A strategy is defined as a plan of action. Teaching strategy includes methods, techniques and materials that are selected to promote learning. The term of teaching and learning strategy represents the teaching and learning process. With a joint program between Indonesia government and the United Nations, the government has implemented a new system of learning which one of the feature is requiring students to .be actively involved in more cooperative and interactive ways of learning, that is, students are supposed to work in groups to achieve shared learning goals. What makes it different from individ11alistic and competitive class? And how the cooperative and interactive ways of learning is conducted.